2013
DOI: 10.1055/s-0032-1333224
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Orbital Tissues in Murine Models of Graves' Disease Reveals Expression of UCP-1 and the TSHR in Retrobulbar Adipose Tissues

Abstract: Over the past decade a number of murine models of Graves? disease (GD) have been described. The full symptom complex, including typical orbital changes, however, could not yet be induced. In this report, we examined the influence of modified immunization protocols on orbital pathology. C57BL/6 and BALB/c mice were immunized against the human TSH receptor (TSHR), using either a TSHR encoding plasmid or a TSHR A-subunit adenovirus. Prior to immunization with the TSHR plasmid, regulatory T cells were depleted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Thyroid gland histology and orbital histology were conducted as described (11,12,16). All serum determinations were in individual mice for T4, anti-TSHR antibodies, and their subtypes, TSAbs and TSBAbs (13,15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid gland histology and orbital histology were conducted as described (11,12,16). All serum determinations were in individual mice for T4, anti-TSHR antibodies, and their subtypes, TSAbs and TSBAbs (13,15).…”
Section: Methodsmentioning
confidence: 99%
“…Although this is an outstanding model for autoimmune thyroid hypertrophy, it does not lead to any orbital manifestations (8,11,19). There are a number of differences in the outcome of the anti-TSHR response between the adenovirus model and the plasmid-in vivo electroporation model described herein.…”
mentioning
confidence: 99%
“…In 2013, Johnson KTM et al [10] have invented a novel technique by removing of the entire mouse orbit and using optic nerve as an anatomical landmark, that increased the sensitivity of retrobulbar detection [10]. Using this technique, Moshkelgosha et al reported that immunized female BALB/c mice with TSHR A subunit expressing plasmids were able to induce GO like phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid—trachea preparations and the entire orbital bony tissues (including the orbital bones with the eyeball, extraocular muscles, and the optic nerve) were collected and fixed in 4% paraformaldehyde[10]. The orbital bony tissue was placed in 10% EDTA decalcification solution for at least 15 days with two changes of the solution.…”
Section: Methodsmentioning
confidence: 99%
“…A few articles have recently described the orbital lesions in the models mentioned above. First, immunization with the human TSHR by either adenovirus or plasmid (without in-vivo electroporation) induced no orbital lesion despite significant expression of the TSHR protein in the orbital fat [21]. Second, adoptive transfer of splenocytes from Admouse TSHR-immunized TSHR knockout mice to nude mice induced macrophage infiltration into the retrobulbar muscles and adipose tissues at low frequency at the end of the experiment when mice are either euthyroid or hypothyroid with positive TBAb (see above) [11 && ].…”
Section: Graves' Orbitopathy Modelmentioning
confidence: 99%